RELEVANCE OF FIBONACCI SEQUENCE IN BIOLOGY - Normoʻminov Ramon G'iyos o'g'li (Web of Journals Publishing, 2024)
The Fibonacci sequence, with its intriguing pattern of numbers (1, 1, 2, 3, 5, 8, 13...), extends beyond the realm of mathematics and finds surprising relevance in the world of biology. This article explores the compelling evidence of the Fibonacci sequence's presence in various biological phenomena, highlighting its role in shaping the natural world.
Keywords: Fibonacci sequence, biology, nature, patterns, growth, development, optimization, self-similarity, fractals, mathematical biology, biomathematics, biological modeling.